Estudio comparativo del rendimiento de tecnologías evpn y vpls en un ambiente simulado utilizando gns3 en la Universidad Técnica de Cotopaxi - Lituma Galarza, Jonathan Paul (2022)
The need that we currently have to have secure networks is almost essential both for individuals and for a large organization, since we have important information that could be stolen or changed. The resolution reached by the network infrastructure developers was to create virtual private networks, in this research project we intend to make a comparison of two technologies of virtual private networks, which are VPLS (Virtual private lan Service) and EVPN (Ethernet VPN ), the two technologies are being used in conjunction with the IP/MPLS protocol that helps them improve the quality of service for time-sensitive applications, also for the purpose of evaluating the performance of data traffic and security, in order to a future to determine which option is viable to implement in the network of the Technical University of Cotopaxi. The methodology of the research project was Top-Down Network Desing, which has four phases: objective business analysis and limitations, logical design, physical design and the testing phase that allowed us to design and develop the topology, the test scenario to compare the two technologies will be the GNS3 simulation software, virtualization environments such as VMWare Player and GNS3 VM will be used, it will allow us to have a better performance in the simulation of all the network devices integrated in the topology, three scenarios of tests that are: network convergence, Mac mobility and boom suppression, to obtain an analysis of the performance and characteristics of each of the technological tools.